2011
DOI: 10.3109/07357907.2011.606248
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Modified Vaccinia Virus Ankara (MVA) Expressing Wild-Type Human p53 Induces Specific Antitumor CTL Expansion

Abstract: The p53 gene product is an attractive target for tumor immunotherapy. The present study aims to understand the potential of MVAp53 vaccine to induce expansion of p53 specific cytotoxic T lymphocyte ex vivo in cancer patients. The result indicated that 14 of 23 cancer patients demonstrated p53 specific IFN-γ production, degranulation, cell proliferation, and lysis of p53 over-expressed human tumor cell lines. These experiments show that MVAp53 stimulation has the potential to induce the expansion of p53 specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Hupki mice immunized with p53MVA showed regression of established 4TI syngeneic breast tumors with murine p53 knockout and engineered human p53 expression, and generation of systemic anti-tumor immunity (15). Finally, studies with PBMC collected from cancer patients with solid tumors showed that specific recall immune responses to p53 could be stimulated in vitro with p53MVA (16). …”
Section: Introductionmentioning
confidence: 99%
“…Hupki mice immunized with p53MVA showed regression of established 4TI syngeneic breast tumors with murine p53 knockout and engineered human p53 expression, and generation of systemic anti-tumor immunity (15). Finally, studies with PBMC collected from cancer patients with solid tumors showed that specific recall immune responses to p53 could be stimulated in vitro with p53MVA (16). …”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical trials with wtMVA as well as recombinant MVA vaccine candidates confirmed the safety of MVA in humans . In line with this, recombinant MVA vaccines have been shown to induce protective immunity in tumor therapy and various infectious diseases .…”
mentioning
confidence: 74%
“…However, clinical benefit could not be demonstrated. Another vaccine, the recombinant modified vaccinia virus Ankara (MVA) expressing wild-type human p53 (MVAp53), was found to induce p53-specific IFN-γ production, degranulation, cell proliferation, and lysis of p53-overexpressed tumor cells [18]. A phase II trial of two different p53 peptide vaccines showed specific immune responses with minimal toxicity in patients with ovarian cancer.…”
Section: Potential Treatments For Tp53 Altered Tumorsmentioning
confidence: 99%